PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS SEARCH SOLVE CREATE (SSCS) PAD MATERI BANGUN DATAR SEGI EMPAT DI KELAS VII SMP NEGERI KARANG DAPO - Rati Auwallah; Efuansyah E; Rani Refianti (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2022)
This study aims to develop a Search Solve Create Share (SSCS) based student worksheet on class VII quadrangular flat building materials. This research is development research using a 4-D development model consisting of 4 stages, namely: the defining stage (define), the planning stage (design), the development stage (develop), and the deployment stage (disseminate). The results showed that the SSCS-based LKS developed met valid and practical criteria. SSCS-based LKS is included in the "valid" criteria based on the assessment of all three experts: linguists, media experts, and material experts with an average score of 3.35. For the analysis of the individual trial assessment, it obtained an average score of 3.35 with the category "valid". As for the results of the analysis of teacher practicality questionnaires and small-scale trials with 6 students, an average score of 3.72 was obtained with the criteria of "very practical".